Prevalence of Post-Traumatic Stress Disorder Caused by War in Veterans - A.M. Rahnejat; P. Dabagi; M. Rabiei; A. Taghva; H. Valipoor; V. Donyavi; M.R. Ebrahimi (Afarand Scholarly Publishing Institute, 2017)
Aims: The post-traumatic stress disorders sometimes continue years after wars. The aim of the study was to estimate the prevalence of post-traumatic stress disorders in the veterans 26 years after the end of Iran-Iraq war. Instrument & Methods: In this cross-sectional study, 341 Iranian veterans were studied in 2014. The subjects were selected via cluster random sampling method. Data was collected using post-traumatic stress disorder checklist-military edition (PCL-M-5), clinician-administered post-traumatic stress disorders scale for DSM-5 (CAPS-5), and a demographic questionnaire. Data was analyzed through descriptive statistics and Pearson correlation coefficient and simultaneous regression analysis tests.   Findings: 82 veterans (24.0%) were with post-traumatic stress disorders diagnostic criteria. In addition, their most prevalent post-traumatic stress disorders symptoms were arousal and reactivity, and negative changes in the cognition and mood, successively. Domographic parameters, including educational level (r=-0.191; p<0.01), age during military services (r=0.046; p<0.05), military services length (r=0.107; p<0.05), and injury and its severity (r=0.347; p<0.01) significantly correlated with post-traumatic stress disorders. In addition, 13% of the post-traumatic stress disorders variance were explained by the demographic parameters (p<0.01). Conclusion: 26 years after the end of Iran-Iraq war, many veterans are with post-traumatic stress disorders, and their most prevalent symptom is arousal and reactivity.